MBRS-26. WHOLE EXOME SEQUENCING OF CIRCULATING TUMOR DNA EXTRACTED FROM THE CEREBROSPINAL FLUID ALLOWS A PANGENOMIC CHARACTERISTISATION OF THE PRIMARY TUMOR. Issue 2 (22nd June 2018) - Chicard, Mathieu; Combaret, Valérie; Danzon, Adrien; Clément, Nathalie; Masliah-Planchon, Julien; Bohec, Mylène; Baulande, Sylvain; Pouponnot, Célio; Frappaz, Didier; Doz, François; Delattre, Olivier; Schleiermacher, Gudrun; et al.
Abstract: BACKGROUND: Liquid biopsies are revolutionary tools to detect tumour-specific genetic alterations in body fluids. Here, we assess whether the circulating tumor DNA (ctDNA) in Cerebral Spinal Fluid (CSF) could be used for tumor genetic profiling of Medulloblastomas (MB). METHODS: We extracted the ctDNA of 4-5 CSF droplets after lumbar puncture from patients with Medulloblastoma (12), or ETMR (1). ctDNA (quantity mean 30ng; range 8-177ng) and matched genomic DNA from primary tumors were sequenced by Whole Exome Sequencing (WES) (Illumina 100PE) using Nimblegen Medexome Capture. SNVs/mutations were called using GATK-UnifiedGenotyper, GATK-HaplotypeCaller and Samtools, and filtered on constitutional DNA from public databases. Copy Number profiles were generated with CNVkits. RESULTS: 10/13 cfDNA WES yielded satisfactory depth (>10x). A mean of 466 (range 93-945) SNVs were detected in the primary tumor and 474 (range 18-922) in the CSF. A mean of 416 (range 18-872) commons SNVs were observed between the cfDNA and the primary tumor, comprising classical Medulloblastoma genes such as SMO or MLL2. Interestingly, several SNVs were observed either in the tumor only (mean 50; range 3-115) or in CSF only (mean 58; range 0-148) suggesting a clonal heterogeneity. For 5 cases, Copy Number profiles were also available, allowing the detection of MYCN amplification in 1 MB or 19q13 miRNA cluster amplification in the ETMR.